Émerger de la fragmentation issue du chaos : la Caraïbe insulaire à l’épreuve des paroxysmes hydrométéorologiques - Françoise Pagney Bénito-Espinal (Caravelle)
The recent occurrence of very intense atmospheric disturbances in the Caribbean islands has shown that the chaos they cause results in an extreme spatial atomization that can last over time. This fragmentation leads to a mosaic of socio-spatial margins, that of communities, neighborhoods, from which it is however possible to restore resilient tools. They represent the foundations for the recovery of the affected communities.